Perception and Behavior of PLWHA towards Out-of-Pocket Costs when Accessing Antiretroviral Treatment - Raihana Nadra Alkaff; Dela Aristi (UIMA Press, 2023)
Out-of-pocket costs are defined as direct and indirect costs when accessing antiretroviral (ARV) treatment at healthcare centers that aren’t subsidized by the government. While ARV treatment can be accessed for free, costs for diagnostic tests, consultation, and treatment for opportunistic infections are the main factor behind the low number of People Living with HIV/AIDS (PLWHA) accessing ARV treatment post-diagnosis. This study aims to understand PLWHA’s behaviors that are related to ARV treatment access based on perceived barriers to out-of-pocket costs. This study used a qualitative approach with 8 PLWHA informants and 1 healthcare worker informant that works at a care, support, and treatment (CST) clinic at a private hospital. This study was conducted for four months from August to November 2021. Results found that behaviors in accessing ARV treatment in PLWHA are influenced by their perceived seriousness of HIV, perceived barriers in the national healthcare insurance referral process, and self-efficacy. Perceived out-of-pocket cost barriers were not identified as the informants’ reason for deciding to start ARV treatment or discontinue ARV treatment. This study recommends increasing the availability of clinical psychologists that can provide psychological support for PLWHA, specifically within the first 6 months of diagnosis, supplemented by peer support groups.